2019
DOI: 10.1039/c8dt05082a
|View full text |Cite
|
Sign up to set email alerts
|

Isostructural phase transition, quasielastic neutron scattering and magnetic resonance studies of a bistable dielectric ion-pair crystal [(CH3)2NH2]2KCr(CN)6

Abstract: Ferroelastic phase transition in novel HOIP crystal with dielectric switchable properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 56 publications
0
27
0
Order By: Relevance
“…3D hybrid metal-formate perovskites, a class of multifunctional materials described by the general formula [A]M II (HCOO) 3 , where A is an ammonium cation and M II denotes a divalent metal cation, caught the attention of materials scientists in a few recent years because of their unusual luminescent, [1,2] ferroelastic, [3,4] ferroelectric, [5][6][7] dielectric, [2,4,8] magnetic [2,9,10] or multiferroic [3,[11][12][13] properties. These properties originate from orderdisorder phase transitions (PTs) that enable utilizing them as molecular switches [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3D hybrid metal-formate perovskites, a class of multifunctional materials described by the general formula [A]M II (HCOO) 3 , where A is an ammonium cation and M II denotes a divalent metal cation, caught the attention of materials scientists in a few recent years because of their unusual luminescent, [1,2] ferroelastic, [3,4] ferroelectric, [5][6][7] dielectric, [2,4,8] magnetic [2,9,10] or multiferroic [3,[11][12][13] properties. These properties originate from orderdisorder phase transitions (PTs) that enable utilizing them as molecular switches [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth adding that the P2 1 /n-P2 1 /n isosymmetric PT is also interesting from the spectroscopic point of view because weak changes of vibrational selection rules are expected in spite of significant structural changes and the associated high change of entropy [2]. Moreover, the isosymmetric and isostructural PTs occurring in the coordination polymers are still poorly understood [16,[22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Herein, the critical factor of designing organic‐inorganic phase transition materials is to search for available organic ammonium cations and suitable inorganic anions, which are liable to occur order‐disorder transition . Based on this strategy, a great number of phase transition compounds with small ammonium cations have been researched in recent years, such as methylammonium, dimethylammonium and ethylammonium, which possess small‐volume and conformational flexible. In 2017, Ioannis Deretzis synthesized the organic–inorganic material CH 3 NH 3 PbI 3 , which undergoes the phase transition in 165 K and 327 K, accompanied by an orthorhombic‐to‐tetragonal and a tetragonal‐to‐cubic lattice modification, the results shown that the orientation of the methylammonium cations is the main factor of the phase transition .…”
Section: Introductionmentioning
confidence: 99%
“…The TGA curve shows that the decomposition temperature of TMFM-1 is as high as 550 K (Fig. S2, ESI†), which is far beyond the previously reported cyano-bridged double perovskites, such as [CH 3 NH 3 ] 2 [KCr(CN) 6 ] (460 K), 40 [(CH 3 ) 3 NOH] 2 [KFe(CN) 6 ] (420 K), 29 [(CH 3 ) 3 NOH] 2 [KCo(CN) 6 ] (464 K) 30 and [(CH 3 ) 2 NH 2 ] 2 [KCr(CN) 6 ] (483 K), 41 proving its good thermal stability. Moreover, when exposed in air for 60 days, the PXRD patterns of TMFM-1 still match well with the simulated one, showing excellent phase stability (Fig.…”
mentioning
confidence: 99%
“…2b, the real part ( ε ′) of the dielectric constant of the TMFM-1 crystal at different frequencies is about 6.3 at 120 K, which is close to the previously reported cyano-bridged perovskites, such as (HIm) 2 [KCo(CN) 6 ] (HIm = imidazolium cation), 42 [CH 3 NH 3 ] 2 [KCr(CN) 6 ] 40 and [(CH 3 ) 2 NH 2 ] 2 [KB(CN) 6 ] (B = Co or Cr). 41,43 During the heating process, the value of ε ′ increases slowly, and then exhibits obvious mutation from 13.5 to 16 in the vicinity of around T c , implying the transition from ferroelastic phase to paraelastic phase. Correspondingly, the imaginary part of the dielectric constant ( ε ′′) at low frequencies has an obvious step-like change at T c , while it is not obvious at high frequencies, especially at 1 MHz (Fig.…”
mentioning
confidence: 99%